Hubungan Tingkat Kecemasan Terhadap Tekanan Darah Pada Pasien Pra Operasi - Yosita Utami, Elsya; Susanto, Amin; Elsi Jerau, Emiliani; Novitaari, Dwi (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Preoperative anxiety can affect physiological conditions in patients, particularly blood pressure. Anxiety increases the release of adrenaline and cortisol, leading to elevated heart rate, vasoconstriction, and potential hypertension. This study aimed to examine the relationship between anxiety level and blood pressure in preoperative patients at RSI Ibnu Sina Padang. A quantitative cross-sectional design was used with 85 respondents selected by purposive sampling from a population of 574 preoperative patients. Anxiety was measured by the APAIS questionnaire and blood pressure with a sphygmomanometer. Data were analyzed using univariate and bivariate analyses with the Chi Square test. Most respondents were aged 26–35 years (24.7%), female (63.5%), with ASA II (58.8%). The highest anxiety level was “severe anxiety” (41.2%), and most had normal blood pressure (63.5%). Statistical test showed a significant relationship between anxiety level and blood pressure (p=0.000). It is concluded that the higher the level of anxiety in preoperative patients, the higher the risk of hypertension, hence early detection of preoperative anxiety is important for maintaining hemodynamic stability.